Mediastinal Ectopic Pancreas with Abundant Endocrine Cells Coexisting with Mediastinal Cyst and Thymic Hyperplasia - Yosinta Snak; Ery Kus Dwianingsih; Auliya Suluk Brilliant Sumpono; Rovi Panji; Afif Rahman; Ahmad Ghozali; Samir S. Amr (Case Reports in Pathology)
Mediastinal ectopic pancreas is a rare condition with only 28 cases reported in the literature. Here we report a 21-year-old female patient who presented with dyspnea and intermittent severe chest pain of 7 years’ duration. Computerized tomography scan (CT-scan) of the chest revealed a mediastinal cyst. The cyst was resected and it demonstrated on histopathological examination the presence of pancreatic tissue with increased number of islets of Langerhans, coexistent with mediastinal cyst and thymic hyperplasia. We made a review of all previously reported cases of this entity.